Digital-twin tool for a drinking water distribution system using augmented reality and EPANET - Ji-Ye Park; Kwang-Ju Kim; Minhyuk Jeung; In-Su Jang; Jung-Won Yu; Mi-Seon Kang; Hyun-Su Bae; Changyoon Jeong; Sang-Soo Baek (Environmental Modelling & Software, 2026)

RXLR effectors from Phytophthora infestans suppress host cell death and promote virulence via nuclear localization in Nicotiana benthamiana - SangA Park; Taewon Kim; Soeui Lee; Ye-Eun Seo; Solhee In; Doil Choi; Joo Hyun Lee (Plant Science, 2026)

Occurrence and composition of PFAS in disposable straws from the Korean Market: quantitative and suspect screening analyses - Hyeri Jeon; Ye-Ju Shin; Ye-In Kim; Dong-Su Kim; Hyewon Shin; Younglim Kho (Environmental Science and Pollution Research, 2025)

Macluraparishin C Enhances Neuroprotection Against Oxidative Stress-Induced Neurodegeneration by Activating the Antioxidant/MAPK Signaling Pathway - Md Shiblee Sadik Sabuj; Md Sadikul Islam; Md Rashedunnabi Akanda; Joonseok Lee; Ryunhee Kim; Seung Hyun Lee; Ye Ji Kim; Jin Min Oh; Hyeon Gyeong Ro; In-Shik Kim; Dongchoon Ahn; Sang-Youel Park; et al. (Molecular Neurobiology, 2025)

Long-acting injectable delivery system comprising ordered mixed drug aggregates with deaggregating and uniformly embeddable viscoelastic -polysaccharide solutions - Jun Soo Park; Dong Gun Lee; Jin Hyuk Myung; Min Young Jeong; In Gyu Yang; Gi Yeong Lee; Ji Won Yeo; Chae Won Park; Jin Hwan Kim; Ye Bin Shin; Myoung Jin Ho; Sung Giu Jin; et al. (Carbohydrate Polymers, 2025)

Helical donor–acceptor bulk heterojunctions for dissymmetric circularly polarized light detection - Inho Song; Jaeyong Ahn; Sang Hyuk Lee; Sangwook Lee; Seoyoung Kim; Ye In Cho; Joon Hak Oh (Chemical Engineering Journal, 2025)

Comparison of biogenic volatile organic compounds emissions from representative urban tree species in South Korea and evaluation of standard emission rate models - Da-Hyun Baek; Ye-Bin Seo; Seong-Ji Yu; In-Young Choi; Sang-Woo Lee; Youn-Suk Son; Trieu-Vuong Dinh; Jo-Chun Kim (Atmospheric Environment, 2024)

Lacticaseibacillus paracasei completely utilizes fructooligosacchrides in the human gut through β-fructosidase (FosE) - Dong-Hyun Jung; In-Young Kim; Ye-Jin Kim; Won-Hyong Chung; Mi-Young Lim; Young-Do Nam; Dong-Ho Seo; Cheon-Seok Park (World Journal of Microbiology and Biotechnology, 2024)

Soil moisture profile estimation under bare and vegetated soils using combined L-band and P-band radiometer observations: An incoherent modeling approach - Foad Brakhasi; Jeffrey P. Walker; Jasmeet Judge; Pang-Wei Liu; Xiaoji Shen; Nan Ye; Xiaoling Wu; In-Young Yeo; Edward Kim; Yann Kerr; Thomas Jackson (Remote Sensing of Environment, 2024)

Maternal PM2.5 exposure is associated with preterm birth and gestational diabetes mellitus, and mitochondrial OXPHOS dysfunction in cord blood - Young-Ah You; Sunwha Park; Eunjin Kwon; Ye-Ah Kim; Young Min Hur; Ga In Lee; Soo Min Kim; Jeong Min Song; Man S. Kim; Young Ju Kim; Young-Han Kim; Sung Hun Na; et al. (Environmental Science and Pollution Research, 2024)
Maternal exposure to fine particulate matter (PM 2.5 ) is associated with adverse pregnancy and neonatal health outcomes. To explore the mechanism, we performed mRNA sequencing of neonatal cord blood. From an ongoing prospective cohort, Air Pollution on Pregnancy Outcome (APPO) study, 454 pregnant women from six centers between January 2021 and June 2022 were recruited. Individual PM 2.5 exposure was calculated using a time-weighted average model. In the APPO study, age-matched cord blood samples from the High PM 2.5 (˃15 ug/m 3 ; n = 10) and Low PM 2.5 (≤ 15 ug/m 3 ; n = 30) groups were randomly selected for mRNA sequencing. After selecting genes with differential expression in the two groups ( p -value < 0.05 and log2 fold change > 1.5), pathway enrichment analysis was performed, and the mitochondrial pathway was analyzed using MitoCarta3.0. The risk of preterm birth (PTB) increased with every 5 µg/m 3 increase of PM 2.5 in the second trimester (odds ratio 1.391, p = 0.019) after adjusting for confounding variables. The risk of gestational diabetes mellitus (GDM) increased in the second (odds ratio 1.238, p = 0.041) and third trimester (odds ratio 1.290, p = 0.029), and entire pregnancy (odds ratio 1.295, p = 0.029). The mRNA-sequencing of cord blood showed that genes related to mitochondrial activity (FAM210B, KRT1, FOXO4, TRIM58, and FBXO7) and PTB-related genes (ADIPOR1, YBX1, OPTN, NFkB1, HBG2) were upregulated in the High PM 2.5 group. In addition, exposure to high PM 2.5 affected mitochondrial oxidative phosphorylation (OXPHOS) and proteins in the electron transport chain, a subunit of OXPHOS. These results suggest that exposure to high PM 2.5 during pregnancy may increase the risk of PTB and GDM, and dysregulate PTB-related genes. Alterations in mitochondrial OXPHOS by high PM 2.5 exposure may occur not only in preterm infants but also in normal newborns. Further studies with larger sample sizes are required.

Performance analysis of heat pipe-based passive in-core decay heat removal system for the small modular reactor design with MARS-KS code - Ji Yong Kim; Ye Yeong Park; In Cheol Bang (Annals of Nuclear Energy, 2023)

Efficient MAPbI3-based perovskite solar cells exceeding 21% efficiency via aging treatment - Dae Woo Kim; Young Wook Noh; Jongmin Han; Hye Seung Kim; Chung Hyeon Jang; Ji A. Hong; Sangmi Park; Min Hyeong Lee; Ye In Kim; Myoung Hoon Song (Chemical Engineering Journal, 2023)

Numerical analysis and correlation of thermohydraulic characteristics of louvered fin-tube heat exchanger - Byeong Kook Yoo; Min Seok Kim; Ye In Bang; Jongwon Kim; Taek Keun Kim (International Journal of Refrigeration, 2023)

Identification of novel missense mutation related with non-syndromic sensorineural deafness, DFNA11 in korean family by NGS - Ye-Ri Kim; Hye-Min Kim; Byeonghyeon Lee; Jeong-In Baek; Kyu-Yup Lee; Hong-Joon Park; Un-Kyung Kim (Genes & Genomics, 2023)

Clinical features and epidemiology of severe fever with thrombocytopenia syndrome in dogs in the Republic of Korea: an observational study (2019–2020) - Sun-Woo Han; Ye-In Oh; Ji-Min Rim; Yoon-Kyoung Cho; Dong-Hoo Kim; Jun-Gu Kang; Kyoung-Seong Choi; Joon-Seok Chae (Veterinary Research Communications, 2022)

Protective effect of berberine chloride against cisplatin-induced ototoxicity - Jong-Heun Kim; Jeong-In Baek; In-Kyu Lee; Un-Kyung Kim; Ye-Ri Kim; Kyu-Yup Lee (Genes & Genomics, 2022)
Background Cisplatin (CP) is an effective anticancer drug broadly used for various types of cancers, but it has shown ototoxicity that results from oxidative stress. Berberine has been reported for its anti-oxidative stress suggesting its therapeutic potential for many diseases such as colitis, diabetes, and vascular dementia. Objective Organ of Corti of postnatal day 3 mouse cochlear explants were used to compare hair cells after the treatment with cisplatin alone or with berberine chloride (BC) followed by CP. Methods We investigated the potential of the anti-oxidative effect of BC against the cisplatin-induced ototoxicity. We observed a reduced aberrant bundle of stereocilia in hair cells in CP with BC pre-treated group. Caspase-3 immunofluorescence and TUNEL assay supported the hypothesis that BC attenuates the apoptotic signals induced by CP. Reactive oxygen species level in the mitochondria were investigated by MitoSOX Red staining and the mitochondrial membrane potentials were compared by JC-1 assay. Results BC decreased ROS generation with preserved mitochondrial membrane potentials in mitochondria as well as reduced DNA fragmentation in hair cells. In summary, our data indicate that BC might act as antioxidant against CP by reducing the stress in mitochondria resulting in cell survival. Conclusion Our result suggests the therapeutic potential of BC for prevention of the detrimental effect of CP-induced ototoxicity.

Resolvin D3 Promotes Inflammatory Resolution, Neuroprotection, and Functional Recovery After Spinal Cord Injury - Juri Kim; Hari Prasad Joshi; Seung Hun Sheen; Kyoung-Tae Kim; Jae Won Kyung; Hyemin Choi; Ye Won Kim; Su Yeon Kwon; Eun Ji Roh; Un Yong Choi; Seil Sohn; Yong Ho Kim; et al. (Molecular Neurobiology, 2021)

Gene Flow from Transgenic PPO-inhibiting Herbicide-resistant Rice to Weedy Rice, and Agronomic Performance by Their Hybrids - Kyong-Hee Nam; Do Young Kim; Ye Seul Moon; In Soon Pack; Soon-Chun Jeong; Kee Woong Park; Chang-Gi Kim (Journal of Plant Biology, 2019)

Cloning, Expression and Characterization of a Highly Active Alcohol Dehydrogenase for Production of Ethyl (S)-4-Chloro-3-Hydroxybutyrate - Yi-Hao Zhu; Cai-Yun Liu; Sha Cai; Li-Bin Guo; In-Won Kim; Vipin C. Kalia; Jung-Kul Lee; Ye-Wang Zhang (Indian Journal of Microbiology, 2019)

Establishment of a high-frequency plant regeneration system from rhizome-derived embryogenic cell-suspension cultures of Curcuma longa L. - Eun Yee Jie; Myung Suk Ahn; Jiyoung Lee; Ye In Cheon; Cha Young Kim; Suk Weon Kim (Plant Biotechnology Reports, 2019)

Correction to: Exocyst Complex Member EXOC5 Is Required for Survival of Hair Cells and Spiral Ganglion Neurons and Maintenance of Hearing - Byeonghyeon Lee; Jeong-In Baek; Hyehyun Min; Seung-Hyun Bae; Kyeonghye Moon; Min-A Kim; Ye-Ri Kim; Ben Fogelgren; Joshua H. Lipschutz; Kyu-Yup Lee; Jinwoong Bok; Un-Kyung Kim (Molecular Neurobiology, 2019)

Exocyst Complex Member EXOC5 Is Required for Survival of Hair Cells and Spiral Ganglion Neurons and Maintenance of Hearing - Byeonghyeon Lee; Jeong-In Baek; Hyehyun Min; Seung-Hyun Bae; Kyeonghye Moon; Min-A Kim; Ye-Ri Kim; Ben Fogelgren; Joshua H. Lipschutz; Kyu-Yup Lee; Jinwoong Bok; Un-Kyung Kim (Molecular Neurobiology, 2018)

Effects of vascular formation during alveolar bone process morphogenesis in mice - Seo-Young An; Ye-Ji Lee; Sanjiv Neupane; Jong-Hwa Jun; Ji-Youn Kim; Youngkyun Lee; Karp-Shik Choi; Chang-Hyeon An; Jo-Young Suh; Hong-In Shin; Wern-Joo Sohn; Jae-Young Kim (Histochemistry and Cell Biology, 2017)

Is there a relationship between PPARD T294C/PPARGC1A Gly482Ser variations and physical endurance performance in the Korean population? - Han-Jun Jin; In-Wook Hwang; Ki-Cheol Kim; Hyun-Ik Cho; Tae-Hwan Park; Yun-A Shin; Ho-Seong Lee; Ji-Hyun Hwang; Ah-Ram Kim; Kwang-Hee Lee; Ye-Eun Shin; Ji-Yeon Lee; et al. (Genes & Genomics, 2016)

Characterization and miRNA-mediated posttranscriptional regulation of vitelline membrane outer layer protein I in the adult chicken oviduct - Sang In Lee; Mi-Ran Ji; Ye-Jin Jang; Mi-hyang Jeon; Jeom Sun Kim; Jin-Ki Park; Ik-Soo Jeon; Sung June Byun (In Vitro Cellular & Developmental Biology - Animal, 2015)

Developmental regulations of Perp in mice molar morphogenesis - Sanjiv Neupane; Wern-Joo Sohn; Girdhari Rijal; Ye-Ji Lee; Sanggyu Lee; Hitoshi Yamamoto; Chang-Hyeon An; Sung-Won Cho; Youngkyun Lee; Hong-In Shin; Tae-Yub Kwon; Jae-Young Kim (Cell and Tissue Research, 2014)

Persistence of Genetically Modified Potatoes in the Field - Chang-Gi Kim; Do Young Kim; Ye Seul Moon; Hyo-Jeong Kim; Dae In Kim; Young Jin Chun; Kee Woong Park; Soon Chun Jeong; Soo Young Kim; Hwan Mook Kim (Journal of Plant Biology, 2010)

Random sequence analysis of genomic DNA of a hyperthermophile: Aquifex pyrophilus - In-Geol Choi; Sang Suk Kim; Jae-Ryeon Ryu; Ye Sun Han; Won-Gi Bang; Sung-Hou Kim; Yeon Gyu Yu (Extremophiles, 1997)